ANALISIS MASALAH TERKAIT OBAT PADA PENGOBATAN ASMA RAWAT JALAN - Amelia Lorensia; Diah Fatmala (Jurnal Ilmiah Manuntung: Sains Farmasi Dan Kesehatan, 2021)
Asthma is a non-communicable respiratory disease that can pose a risk of mortality and morbidity. Asthma is a long-term disease that carries the risk of drug-related problems (DRP). This study aims to analyze drug-related problem (MTP) in outpatient asthma treatment. This study used a cross-sectional analysis method using purposive sampling technique, carried out at a Pratama pharmacy in Wonokromo district, Surabaya City. The research sample was adult outpatient asthma patients who underwent treatment at the pharmacy from November 2018 to January 2019. Data were analyzed using GINA and Classification for Drug related problems. The results showed that of the 40 respondents the DRP was 34 respondents (85.00%). The domain related to the effectiveness is that the drug effect is not optimal (88.24%) and other drugs are not needed (11.76%) and the cause of drug selection is the improper combination of drugs (2.87%). And the associated therapy was most involved in DRP events. Outpatient asthma drug use was the most associated therapy for the short acting beta 2 agonist class of drugs. Therefore, inpatient asthma treatment requires monitoring by a pharmacist to achieve optimal treatment.